2008
DOI: 10.1111/j.1365-2664.2008.01474.x
|View full text |Cite
|
Sign up to set email alerts
|

Future novel threats and opportunities facing UK biodiversity identified by horizon scanning

Abstract: Summary Horizon scanning is an essential tool for environmental scientists if they are to contribute to the evidence base for Government, its agencies and other decision makers to devise and implement environmental policies. The implication of not foreseeing issues that are foreseeable is illustrated by the contentious responses to genetically modified herbicide‐tolerant crops in the UK, and by challenges surrounding biofuels, foot and mouth disease, avian influenza and climate change. A total of 35 represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 50 publications
1
111
1
3
Order By: Relevance
“…In their study of the threats facing UK biodiversity, Sutherland et al (2008) identified the decline in people's engagement with nature as having the potential to reduce environmental knowledge and concern. If, as our study suggests, awareness of tree health issues is enhanced through engagement with nature then the apparent decline in engagement is of concern.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of the threats facing UK biodiversity, Sutherland et al (2008) identified the decline in people's engagement with nature as having the potential to reduce environmental knowledge and concern. If, as our study suggests, awareness of tree health issues is enhanced through engagement with nature then the apparent decline in engagement is of concern.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional wisdom enshrined in the work of Peace [13], conducted over many decades, appeared to be the final word on the subject of DED. 3 The community of tree pathologists based at Alice Holt was slow to question this paradigm in the face of conflicting evidence. As Clive Brasier, a senior plant pathologist, acknowledged in interview with us 'it was very difficult to avoid being influenced by Peace because he was very authoritative: he was a fine scientist and a tremendous observer' (interview with Brasier [5]).…”
Section: Reconstructing the Uk Dutch Elm Disease Epidemicmentioning
confidence: 99%
“…The result is that trees and woodland in the UK are arguably under greater threat today from invasive pathogens than ever before [3,4]. The sudden oak death pathogen, P. ramorum (Pr), is thought to have first arrived in the UK as a single introduction, probably on infected nursery stock originating from within the EU [22].…”
Section: The Continuing Contemporary Relevance Of Dutch Elm Diseasementioning
confidence: 99%
See 2 more Smart Citations